2016
DOI: 10.4055/cios.2016.8.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Biportal Endoscopic Spinal Surgery for Recurrent Lumbar Disc Herniations

Abstract: The major problems of revision surgery for recurrent lumbar disc herniation (LDH) include limited visualization due to adhesion of scar tissue, restricted handling of neural structures in insufficient visual field, and consequent higher risk of a dura tear and nerve root injury. Therefore, clear differentiation of neural structures from scar tissue and adhesiolysis performed while preserving stability of the remnant facet joint would lower the risk of complications and unnecessary fusion surgery. Biportal endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…Disc herniation can changes of the lumbar spine and lead to leg pain and associated clinical symptoms, with the potential to severely impair function and quality of life. [1,30,31] The rationale of management of disco genic pain must be based on accurate diagnosis, for lumbar nerve root pain radiates in the distribution of one or more dermatomes and may be associated with neurological deficits. [32,22,19,10] The painful condition of the disc is currently identified by preoperative diagnostic, and the endoscopic not only procedure in the big disc herniation with leg pain, but also the small disc herniation with sciatica may be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disc herniation can changes of the lumbar spine and lead to leg pain and associated clinical symptoms, with the potential to severely impair function and quality of life. [1,30,31] The rationale of management of disco genic pain must be based on accurate diagnosis, for lumbar nerve root pain radiates in the distribution of one or more dermatomes and may be associated with neurological deficits. [32,22,19,10] The painful condition of the disc is currently identified by preoperative diagnostic, and the endoscopic not only procedure in the big disc herniation with leg pain, but also the small disc herniation with sciatica may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of minimally invasive endoscopic methods in spine surgery, a number of techniques have recently been developed that are applicable in the treatment of lumbar disc herniation. [1][2][3][4][5][6] The current trend of evolution lumbar spinal surgery has been toward endoscopic discectomy, which is a minimally invasive treatments aimed at removing nuclear material and decompression the nerve through devices were inserted percutaneous into intervertebral discs. [7,8] Endoscopic discectomy is a well-established technique for nerve decompression by transforaminal to access the disc space, and transforaminal endoscopic lumbar discectomy has become population for its advantages and matured with time.…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure and heart rate were stable, and arterial blood gas (ABG) test was performed every 1.5 hours. The final ABG analysis was carried out 30 minutes before turning the patient back to the supine position; the results indicated satisfactory results (pH, 7.42; PaCO 2 , 46 mmHg; PaO 2 , 300 mmHg; BE, 4.1 mmol/L; HCO 3 , 29 mmol/L; and SaO 2 , 99%). The patient had a 400-mL urinary output.…”
Section: Case Presentationmentioning
confidence: 99%
“… 8 9 10 11) Recently, studies on spinal surgery using the unilateral biportal endoscopic technique have been reported by several authors. 12 13 14) To date, few studies reported the results of over a year of follow-up after farlateral decompression using unilateral biportal endoscopic technique in foraminal stenosis. This study was to evaluate the clinical and radiological outcomes of far-lateral decompression using unilateral biportal technique.…”
mentioning
confidence: 99%